ELECTRONIC COMMERCE (E-COMMERCE): COUNTERPOINTS OF THE ADHESION CONTRACT AND THE CONSUMER DEFENSE CODE (LAW 8.078/90) - Pinho de Rezende, Erickson (Revista Gênero e Interdisciplinaridade, 2023)
The work in question here aims to show how contracts are the basis for carrying out electronic commerce or E-commerce, since its rule is also based on the Consumer Defense Code (CDC), Law 8.078/90. In addition, it will clarify how to use contracts to obtain any other asset. The adhesion contract, the focus of our study, is a contract carried out where only one of the parties is willing to assume the risk of the thing, which is generally a movable good and almost always an electronic good that is easily deteriorated. Knowing this, it is up to those who have a little clarification and study, to show that today with the Consumer Defense Code (CDC), people have a framework of rules and laws that protect and support their protection. For its elaboration, this research will be carried out through bibliographical references of renowned authors, who are the ones we base ourselves on for the study of the subject discussed here.